Utviklingen av den lokal- og regionalhistoriske forskningen i Nord-Norge og Nord-Russland i perioden 1972-2015. En komparativ historiografi. - Andersson, Ola Goverud (UiT Norges arktiske universitet, 2019)
This thesis is a comparative historiography of local- and regional historical research in Northern Norway and Northwest Russia in the period 1972–2015. The analysed source material consists of local- and regional historical accounts, written by historians at the universities of Tromsø, Murmansk and Arkhangelsk. The text analysis entails close reading of central texts from these three research traditions. Employing both diachronic and synchronic comparison, the author identifies both differences and similarities between these traditions. The distinguishing charecteristics of these traditions are systematically analysed through observation of their ‘central topics’, ‘central motives’ and ‘articulated and/or applied methodology and theory’. Primary analysis of the texts builds upon a hermeneutic tradition, while the comparative element of the analysis applies conceptual history and translation theory. Upon these premises, the author investigates whether the three text- and research traditions envisage certain regional historical traits as typical, prevailing or enduring, and whether the texts in this or other aspects can be seen as promoting one of several suggested forms of ‘cultural regionalism’. Additionally, this comparative historiography on research traditions in Tromsø, Murmansk and Arkhangelsk addresses questions concerning the unique tradition of cooperative projects between historians of Northern Norway and Northwest Russia that began in 1986. The contacts and common projects have to some degree interwoven the three research traditions, and the author therefore tests the hypothesis that the collaboration between the Norwegian and Russian historians in the North has facilitated exchange and the mutual influence of thematic orientations and analytical perspectives.